CURRENT REVIEW OF TREATMENTS FOR INSOMNIA: EFFECTIVENESS, EFFICACY AND ADVANCES - Adrianna Kaczmarek; Franciszek Szweda; Tomasz Poczwardowski; Katarzyna Anna Kowalska; Jakub Tomasz Latos; Marcin Chwalczuk; Olivia Grygorcewicz; Marta Koneczna; Karolina Alicja Krystyniak; Kinga Augustyniak (International Journal of Innovative Technologies in Social Science, 2025)
This narrative review aimed to synthetically evaluate the current efficacy of pharmacological and non-pharmacological methods for treating chronic insomnia, to identify their risk profiles, and to determine the future prospects and chances for the development of modern therapeutic strategies. Methods: A literature analysis was conducted, encompassing key clinical trials and systematic reviews concerning Cognitive Behavioral Therapy for Insomnia (CBT-I), hypnotics (BDZs, NBDZAs, DORAs), and innovative treatment modalities (neuromodulation, novel molecules, diet, stimulants, physical avtivity). Key findings: The analysis demonstrated that CBT-I invariably remains the first-line therapy and gold standard, showing durable efficacy in improving objective and subjective sleep parameters (latency, total sleep time, quality) while minimizing the risk of dependence, in contrast to pharmacotherapy. Pharmacological methods, due to their lower safety profile, are considered second-line therapy. A significant advance in this area is the introduction of Dual Orexin Receptor Antagonists (DORAs), such as daridorexant, which is safe and well-tolerated in long-term treatment, filling a gap left by older hypnotics. Active development of innovative techniques (e.g., NIBS, VeNS) was also noted, but their implementation is hindered by a lack of protocol standardization and insufficient clinical evidence. Conclusions: CBT-I is the optimal strategy for insomnia management. However, further research on its long-term efficacy is essential. Future studies should focus on implementing sequential therapies and developing DORAs and neuromodulation techniques for personalized treatment. Regardless of the intervention, comprehensive sleep hygiene is crucial for maintaining remission.